The Effect Of Audit Complexity Of Budget Pressure Time And Auditor Experience On Audit Quality With An Understanding Of Information Systems As A Moderate Variable - L.G.P Sri Eka JAYANTI; Putu Gede Wisnu Permana KAWISANA (Indonesia Strategic Sustainability, 2022)
The development of the world of accounting requires every accountant to use a system to make financial statements. The number of accountants in each company has also become small, along with the development of financial statements that are already paperless. It is also experienced for a public accountant where every audit activity must be able to understand information technology. So that in every audit process, every client who uses a qualified financial system can be followed by the auditor concerned. This study aims to determine the influence of task complexity, budget time pressure, and auditor experience on audit quality. This study uses the understanding of information systems as a moderation variable to determine whether the relationship between the three variables can strengthen audit quality by understanding the information system for an auditor. This research was conducted at a Public Accounting Firm in Bali, with a sample determination method based on criteria. This study is looking for auditors with more than one year of experience as a sample of respondents. The regression tool used is moderation regression. The results of this study involved 56 respondents from 11 public accounting firms in Bali, understanding that the information system could not moderate the relationship of audit complexity to audit quality. Understanding information systems can weaken the relationship of time budget pressures to audit quality, and understanding information systems can also strengthen the relationship of work experience to audit quality.